Mindfully Scrolling: Rethinking Facebook After Time Deactivated - Baym, Nancy; Wagman, Kelly; Persaud, Christopher (Social Media + Society, 2020)
Many people express concern that Facebook’s users are overly connected. This article examines responses to survey questions asked after a large random sample of American Facebook users had been paid to deactivate Facebook. We find a recurring discourse of mind including, for example, references to mindfulness. Using iterative qualitative coding, we ask what meanings and practices are invoked in this discourse. Furthermore, we critically assess the potential of what respondents describe to address the problems of overconnection. We find explicit awareness of the automaticity of use, the value and content of Facebook, and how it makes users feel. We find that users came to practice disconnection at many nested levels of vernacular affordances. Ultimately, we argue that Facebook has become a landscape trap, altering daily life such that individual practices, such as mindful scrolling, cannot overcome the overconnection problems it may create. Mindfulness in this discourse may be power, but it is power to avoid elements of Facebook, not power to transform it.